Patient-centred innovation to ensure access to diabetes care in Cambodia: the case of MoPoTsyo. Issue 1 (December 2016) - van Olmen, Josefien; Eggermont, Natalie; van Pelt, Maurits; Hen, Heang; de Man, Jeroen; Schellevis, François; Peters, David; Bigdeli, Maryam
Abstract Background The increasing prevalence of chronic diseases puts a high burden on the health care systems of Low and Middle Income Countries which are often not adapted to provide the care needed. Peer support programmes are promoted to address health system constraints. This case study analyses a peer educator diabetes programme in Cambodia, MoPoTsyo, from a health system's perspective. Which strategies were used and how did these strategies change? How is the programme perceived? Methods Data were collected through semi-structured interviews with patients, MoPoTsyo staff and peer educators, contracted pharmacy staff and health workers, health care workers and non-contracted pharmacists and managers and policy makers at district, provincial and national level. Four areas were purposively selected to do the interviews. An inductive content analysis was done independently by two researchers. Results MoPoTsyo developed into three stages: a focus on diabetes self-management; a widening scope to ensure affordable medicines and access to other health care services; and aiming for sustainability through more integration with the Cambodian public system and further upscaling. All respondents acknowledged the peer educators' role and competence in patient education, but their ideas about additional tasks and their place in the system differed. Indirectly involved stakeholders and district managers emphasized the particular roles and responsibilities of all actors in the system and the particular role of the peer educator in the community. MoPoTsyo's diagnostics and laboratory services were perceived as useful, especially by patients and project staff. Respondents were positive about the revolving drug fund, but expressed concerns about its integration into the government system. The degree of collaboration between health care staff and peer educators varied. Conclusion MoPoTsyo responds to the needs of people with diabetes in Cambodia. Key success factors were: consistent focus on and involvement of the target group, backed up by a strong organisation; simultaneous reduction of other barriers to care; and the ongoing maintenance of relations at all levels within the health system. Despite resistance, MoPoTsyo has established a more balanced relationship between patients and health service providers, empowering patients to self-manage and access services that meet their needs.